Clinical Implications of the New York Heart Association Classification. Issue 23 (3rd December 2019) - Caraballo, César; Desai, Nihar R.; Mulder, Hillary; Alhanti, Brooke; Wilson, F. Perry; Fiuzat, Mona; Felker, G. Michael; Piña, Ileana L.; O'Connor, Christopher M.; Lindenfeld, Joanne; Januzzi, James L.; Cohen, Lawrence S.; et al.
Abstract : Background: The New York Heart Association (NYHA) classification has served as a fundamental tool for risk stratification of heart failure (HF) and determines clinical trial eligibility and candidacy for drugs and devices. However, its ability to adequately stratify risk is unclear. Methods and Results: To compare NYHA class with objective assessments and survival in patients with HF, we performed secondary analyses of 4 multicenter National Institutes of Health–funded HF clinical trials that included patients classified as NYHA class II or III: TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist), DIG (The Effect of Digoxin on Mortality and Morbidity in Patients With Heart Failure), HF‐ACTION (Efficacy and Safety of Exercise Training in Patients With Chronic Heart Failure), and GUIDE‐IT (Guiding Evidence‐Based Therapy Using Biomarker Intensified Treatment in Heart Failure). Twenty‐month cumulative survival was compared between classes using Kaplan–Meier curves and the log rank test. NT‐proBNP (N‐terminal pro–B‐type natriuretic peptide), Kansas City Cardiomyopathy Questionnaire (KCCQ) scores, 6‐minute walk distances, left ventricular ejection fraction, and cardiopulmonary test parameters were compared using Wilcoxon rank sum tests and percentage overlap using kernel density estimations. Cumulative mortality varied significantly across NYHA classes and HF clinical trials (likelihood ratio, P <0.001). Mortality at 20 months for NYHA class II ranged from 7% for patients in HF‐ACTION to 15% in GUIDE‐IT, whereas mortality for NYHA class III ranged from 12% in TOPCAT to 26% in GUIDE‐IT. There was substantial percentage overlap in values for NT‐proBNP levels (79% and 69%), KCCQ scores (63% and 54%), 6‐minute walk distances (63% and 54%), and left ventricular ejection fraction (88% and 83%). Similarly, there was substantial overall in values for minute ventilation–carbon dioxide production relationship (71%), maximal oxygen uptake (54%), and exercise duration (53%). Conclusions: The NYHA system poorly discriminates HF patients across the spectrum of functional impairment. These findings raise important questions about the need for improved phenotyping of these patients to facilitate risk stratification and response to interventions.